2013
DOI: 10.1186/1749-8090-8-228
|View full text |Cite
|
Sign up to set email alerts
|

The ascending aortic image quality and the whole aortic radiation dose of high-pitch dual-source CT angiography

Abstract: BackgroundAortic dissection is a lift-threatening medical emergency associated with high rates of morbidity and mortality. The incidence rate of aortic dissection is estimated at 5 to 30 per 1 million people per year. The prompt and correct diagnosis of aortic dissection is critical. This study was to compare the ascending aortic image quality and the whole aortic radiation dose of high-pitch dual-source CT angiography and conventional dual-source CT angiography.MethodsA total of 110 consecutive patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
1
15
0
2
Order By: Relevance
“…Multislice computed tomography angiography (CTA) has become the preferred method to assess aortic diseases [ 1 6 ]. However, X-ray radiation and iodine hazards are the major concern associated with CTA, as repeat CTA scans are commonly performed during pre- and postoperative assessments of aortic disease [ 7 9 ]. To address these concerns, clinical studies have recently reported the use of the second-generation dual-source computed tomography (DSCT) Flash protocol for dose reduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multislice computed tomography angiography (CTA) has become the preferred method to assess aortic diseases [ 1 6 ]. However, X-ray radiation and iodine hazards are the major concern associated with CTA, as repeat CTA scans are commonly performed during pre- and postoperative assessments of aortic disease [ 7 9 ]. To address these concerns, clinical studies have recently reported the use of the second-generation dual-source computed tomography (DSCT) Flash protocol for dose reduction.…”
Section: Introductionmentioning
confidence: 99%
“…High-pitch CTA of the aorta was shown to reduce radiation exposure by 45–50% and to allow the use of less contrast medium (CM) while maintaining vessel attenuation at a diagnostic level [ 12 ]. Liu et al reported that DSCT can provide motion artifact-free imaging of the ascending aorta at a low radiation dose compared to the conventional protocol [ 7 ]. However, that study used a CM with a high concentration of iodine (370 mg I/mL).…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the X-ray radiation hazards and the amount of iodine hazards, high-pitch scanning mode, lowering tube voltage and low-concentration CM are combined. IR technology is used to overcome a limitation that low tube voltage may result in increased noise, and to improve image quality [15]. To our knowledge, this is the first report of demonstrating the use of CTA of low-concentration CM (270mg I/mL) combined low radiation dose and IR showing the rare concomitance with good image quality, and the recorded case of AAA regular surveillance with a native pelvic kidney.…”
Section: Discussionmentioning
confidence: 90%
“…This may be helpful for improved differentiation between ascending aortic dissection and motion artifacts. This potential advantage of high-pitch acquisition for aortic CTA has been reported in several recent studies, 6,10,26,27 further emphasizing the relevance of non-ECG-triggered high-pitch CTA for the detection of thoracic aortic diseases, especially for precise characterization of the proximal extent of dissection, intramural hematoma and the involvement of coronary artery ostia. 6 However, we also noted some potential issues regarding image quality assessment when using the 70-kVp CTA protocol.…”
Section: Discussionmentioning
confidence: 90%